HUBUNGAN ANTARA SUSTAINABILITY REPORT, KINERJA PASAR, DAN KINERJA FUNDAMENTAL: BUKTI AKTOR KEPEMILIKAN PERUSAHAAN - Luthpiyah Juliandara; Siti Jahroh; Budi Purwanto (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
The importance of concern for the environment in long-term business processes and the sustainability of the company's life through the practice of sustainability report disclosure. This study aims to analyze the effect of the sustainability report and actors of company ownership on market performance and fundamental performance. The sampling technique was purposive sampling. Types and sources of data used are secondary data from annual reports and sustainability reports. The method used is factor analysis to see the contribution of indicators to variables, and path analysis to see the effect of sustainability report disclosure, using Statistical Product and Service Solutions (SPSS) tools. The findings state that the sustainability report has an effect on market performance, but the sustainability report has no effect on fundamental performance. Company ownership: BUMN and BUMS actors influence market performance and company fundamental performance. Keywords: BUMN, BUMS, market performance, fundamental performance, sustainability report